Masihkah Kinerja Keuangan Dianggap Penting Dalam Menentukan Kebijakan Dividen? - Klaudia Stephanie Ginting; Nisrul Irawati; Chairul Muluk (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the effect of liquidity ratios, activity, leverage, and company size on dividend policy through the financial performance of consumer non-cyclical companies for the 2017-2021 period. Methodology/approach: The sampling technique using purposive sampling method obtained 27 companies as research samples. Data analysis techniques using panel data analysis and path analysis. Findings: The results showed that liquidity (CR) and financial performance (ROA) had a significant negative effect on dividend policy (DPR). Total Asset Turnover has a significant positive effect on dividend policy (DPR). Leverage (DER) and firm size have no significant effect on dividend policy (DPR). Liquidity (CR) and Total Assets Turnover have a significant positive effect on financial performance (ROA). Leverage (DER) and company size have no significant effect on financial performance (ROA). Liquidity (CR), leverage (DER), and company size on dividend policy (DPR) through financial performance (ROA) have no significant effect. Meanwhile, total asset turnover on dividend policy (DPR) through financial performance (ROA) has a significant influence. Practical and Theoretical contribution/Originality: This research is expected to contribute to increasing Dividend Policy (Dividend Payout Ratio), companies must increase company sales activities so that company revenues can be greater than company expenses and companies have positive free cash flow which indicates good financial performance so they can distribute cash dividends. to shareholders. Research Limitation: This research is limited to the use of financial performance intervening variables only and focuses on consumer non-cyclicals subsector companies listed on the IDX in 2017-2021.